1998
DOI: 10.1152/jappl.1998.85.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Identical responses of fast muscle to sustained activity by low-frequency stimulation in young and aging rats

Abstract: To investigate effects of sustained activity on major phenotypic properties, the left extensor digitorum longus muscle of young (15 wk) and aging (101 wk) male Brown Norway rats was subjected to 50 days of chronic low-frequency stimulation (CLFS; 10 Hz, 10 h/day). The contralateral muscle served as control. Changes in metabolic enzymes were analyzed by using glyceraldehyde-3-phosphate dehydrogenase and lactate dehydrogenase as reference enzymes of glycolysis and by using citrate synthase and 3-hydroxyacyl-CoA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…Previous studies have demonstrated that a relative decrease in the type IIb MHC isoform of rat fast muscle is induced by the increase in muscle activity that occurs in physical training or upon electric stimulation (Demirel et al 1999;Sullivan et al 1995;Sˇkorjanc et al 1998). Our data are in agreement with those previous results in that the percentage of the type IIb MHC isoform in PLA in each VE group was significantly lower than that in the corresponding SC group (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that a relative decrease in the type IIb MHC isoform of rat fast muscle is induced by the increase in muscle activity that occurs in physical training or upon electric stimulation (Demirel et al 1999;Sullivan et al 1995;Sˇkorjanc et al 1998). Our data are in agreement with those previous results in that the percentage of the type IIb MHC isoform in PLA in each VE group was significantly lower than that in the corresponding SC group (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased aconitase levels agreed with a previous study which suggests that oxidative damage during aging targets mitochondrial aconitase (56). Interestingly, previous metabolic studies comparing chronic low-frequency stimulated young versus aged fibres suggest that both muscle types respond in a similar way to sustained neuromuscular activity (57,58). Therefore, the age-induced changes in glycolytic and mitochondrial enzymes might be a consequence of altered innervation patterns and not a primary pathological insult within the skeletal muscle fibres themselves.…”
Section: Discussionsupporting
confidence: 89%
“…Yet, by 90 days, young and aged animals had equivalent levels of this mitochondrial enzyme marker. In another study, CCA over 50 days effectively increased mitochondrial content and reduced the number of COX-deficient fibers in aged muscle (125,150). These data illustrate the potential corrective nature of chronic exercise in ameliorating ETC dysfunction but also suggest that the kinetics of mitochondrial adaptations in old muscle are delayed in response to an exercise regimen.…”
Section: Mitochondrial Adaptations With Exercise In Aging Musclementioning
confidence: 76%